Clinical experience of upper limb ischemia: a retrospective study - Tolia, Jitesh; Bhatt, Arvind (International Surgery Journal, 2020)
Background: Arterial disorders of the upper extremity are much less common than those of the lower extremity, but when they result in symptoms of acute or chronic ischemia, surgical or endovascular techniques for upper extremity revascularization may be needed. This study presents a review of the epidemiology, aetiology, and clinical characteristics of upper limb ischemia. Methods: The records of 70 patients with upper limb ischemia who underwent treatment from were retrospectively reviewed. Results: A total of 44 patients were diagnosed by CT. Other diagnostic methods and tools used were conventional angiography and duplex ultrasound. Four cases were diagnosed solely on the basis of a medical history and physical examination. A total of 56 surgeries were performed. Rest of the 14 patients went under conservative therapy. The operations included embolectomy and thrombectomy using a Fogarty balloon catheter (n=32), bypass surgery using the great saphenous vein (n=10), percutaneous catheter-directed thrombolysis (n=8), and primary repair (n=4). Patients with Raynaud’s phenomenon or Burger’s disease were either treated with medication only (n=14) or with sympathectomy (n=2). Conclusions: The duration of symptoms in cases of upper limb ischemia may vary from two hours to a year, depending on the aetiology and severity of the illness. Many debates have addressed whether the time gap between the onset of symptoms and treatment predicts long-term arm function.